2024
DOI: 10.1097/md.0000000000036804
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 supplementation and outcomes of heart failure: A systematic review of clinical trials

Mahin Nomali,
Mohammad Eghbal Heidari,
Aryan Ayati
et al.

Abstract: Backgrounds: Omega-3 supplements are endorsed for heart failure (HF) patients to reduce hospitalizations and mortality, offering anti-inflammatory and cardioprotective benefits. Methods: A comprehensive search was conducted in various databases until November 2022. Eligible studies included clinical trials on patients with HF. Data extraction covered study details, omega-3 specifics, outcomes, and limitations. The JADAD scale was used to assess the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…A large number of previous studies indicated that ω3 polyunsaturated FA are essential for normal growth and development. The health effects of these FAs include reduction of cardiovascular risk due to antiarrhythmic, anti-inflammatory, anti-thrombotic and lipid lowering actions, as well as improved glucose level control and insulin sensitivity, and neuroprotection [34][35][36][37]. Thus, reduced ACSBG1 expression could be associated with improvement in cardiovascular disease, reduced complications of diabetes and lowered risk for depression.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of previous studies indicated that ω3 polyunsaturated FA are essential for normal growth and development. The health effects of these FAs include reduction of cardiovascular risk due to antiarrhythmic, anti-inflammatory, anti-thrombotic and lipid lowering actions, as well as improved glucose level control and insulin sensitivity, and neuroprotection [34][35][36][37]. Thus, reduced ACSBG1 expression could be associated with improvement in cardiovascular disease, reduced complications of diabetes and lowered risk for depression.…”
Section: Discussionmentioning
confidence: 99%